The Full Impact of Energy Efficiency on Households' Energy Demand - Kurt Kratena; Michael Wüger (Austrian Institute of Economic Research (WIFO), 2010)
This paper deals with technical progress in the energy efficiency of US households' capital stock (appliances and passenger cars) and its potential for energy saving. An increase in the energy efficiency of households can only be achieved via a different capital stock. The link between the average energy efficiency and the stock of energy-using durables is econometrically estimated based on a new data set of household appliances and passenger cars. This relationship complements a Quadratic Almost Ideal Demand System (QUAIDS) for six consumption categories (non-durables), including heating, electricity and transport. Any increase in energy efficiency lowers the corresponding "service" price and leads to a "rebound effect". A simulation exercise shows how the ceteris paribus-rebound effect is changed by taking into account the capital costs and other interdependencies and feedbacks that can only be captured by a full model of household demand.
Keywords: 330; household energy demand; embodied and induced technical change; rebound effect; Energiekonsum; Privater Haushalt; Technischer Fortschritt; Energieeinsparung; Nachfragesystem; USA